PRE-FEASIBILITY OF MALACCA STRAIT CROSSING - M. Sjahdanulirwan; A. Tatang Dachlan (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Indonesian trading development rapidly shows an improvement with neighbour countries such as Malaysia and Singapore. Even though the transportation infrastructures arround Malacca Straits are currently just provided by boats. For balancing the develpoment trading reasons, Indonesian Government concerns to facilitate the building of transportation infrastructures or a fix-link infrastructure, a crossing bridge between Sumatera island (Indonesia) and Malaysia. Malacca Strait Bridge (MSB) between Indonesia and Malaysia is a part of Trans Asia road link, has been planned since years ago. To support the current planning, the Research and Development Agency – Ministry of Public Works – Republic of Indonesia (Badan Penelitian dan Pengembangan, Kementerian Pekerjaan Umum, Indonesia) needs to make a reviewing on a pre-feasibility study (Pre FS) for MSB. Pre FS activity involved many disciplines of knowledge especially for road/corridor, transportation, bridge, geotechnical, sea shore, environment, and social-economic-culture-policy. Pre-FS results that break event point for Corridor I among Dumai-P.Rupat-P.Medang-Malaysia may be expected between 25 and 30 yeras based on Benefit Cost Ratio methode, using cable stayed and suspension bridges and girders. The longest span for cable stayed and suspension bridges are 2600 m and 1280 m respectively. The selected corridior must be intensively discussed about technology absorbed and safety factor, resources capability for maintenance, integration within toll road network, foundation technology in the sea, and users psychology and comfort. Consession for operator may apply for 30 to 40 years. Keywords: Pre-feasibility study, Strait crossing, Strait bridge, Strait tunnel, Malacca strait bridge, Benefit cost ratio (BCR)